Carer involvement in the transition from inpatient to community mental healthcare: Experiences of stakeholders - A. Kouroupa; E. Petkari; D. Giacco (European Psychiatry, 2022)
Introduction The involvement of informal carers (family and friends) in the care of people with severe mental illness (SMI) contributes to positive clinical outcomes, such as relapse prevention and symptom reduction. To date, the care pathway between inpatient and community care is not clearly defined impeding the smooth transition for patients, whilst carers are still barely involved in shared decision-making processes.